Thermal and Spectral Characterization of Co(II) and Cu(II) Dinonyldithiophosphates: Removal of Co(II) and Cu(II) from Aqueous Solutions - Gumgum, H.B.; Biricik, Nermin (Asian Journal of Chemistry, 2015)
Dinonyldithiophosphoric acid (HDDTP) was prepared by addition of phosphorus pentasulphide to nonyl alcohol. Dinonyldithiophosphate complexes of Co(II) and Cu(II) with general formula [M(DDTP)2] [M = Co(II) or Cu(II)] were prepared by mixing solutions of M(II) with dinonyldithiophosphoric acid in ethanol at room temperature. The acid and its complexes were caharacterized by elemental analysis and infrared, ultraviolet-visible and inductively coupled plasma-optical emission spectrometry. The thermal behaviour of M(DNDTP)2 was investigated by thermogravimetric analysis under a nitrogen atmosphere. Removal of Co(II) and Cu(II) from aqueous media by dinonyldithiophosphoric acid solutions were investigated. The optimum conditions for extraction, such as the organic solvent, pH of the aqueous phase, time of equilibration, concentration and effect of anions, were studied. It was found that dinonyldithiophosphoric acid is an effective substance for removing Cu(II) and Co(II) from aqueous solutions.